KOMUNIKASI INTERRELIGIUS: TELAAH TAFSIR QS. AL-AN’AM AYAT 108 - Ela Indah Dwi Syayekti,; Shinta Nurrohmah,; Nisa Afifah, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2023)
Currently, the inter-religious tolerance movement is being called upon, considering the many religious conflicts that have occurred in Indonesia. Tolerance is a form of respect and not imposing will on others. However, currently, there are still many cases of insulting other religions, both in terms of offerings or ways of worship. This happens because there is still fanaticism and radicalism which considers the teachings of one's own religion to be the most correct, considering the teachings of other religions to be heretical or infidel because they are different from their religion. This study aims to explain how ethics communicates with other religions. Literature research is used as a method in this study, namely by collecting and analyzing the interpretations of the verses used. The results of this study are QS. al-An'am (6): 108 gives advice to Muslims not to insult God and the teachings of other religions even though they are emotional or feel disturbed. Not only in cases of idols but also in other religions. On the other hand, Muslims must communicate in a polite and gentle way so that sympathy from other religions arises and good relations are established.